Effectiveness of Dry Needling in Improving Pain and Function in Comparison with Other Techniques in Patients with Chronic Neck Pain: A Systematic Review and Meta-Analysis - Mar Hernández-Secorún; Hugo Abenia-Benedí; Sergio Borrella-Andrés; Isabel Marqués-García; María Orosia Lucha-López; Pablo Herrero; Isabel Iguacel; José Miguel Tricás-Moreno; César Hidalgo-García (Pain Research and Management)
The purpose of this systematic review and meta-analysis was to assess the short-, mid-, and long-term effectiveness of dry needling in improving pain and functional capacity of patients with chronic neck pain. Search strategy was performed on PubMed, Web of Science, Scopus, PEDro, and Cochrane Library Plus biomedical databases. The risk of bias was assessed using the RoB2 tool. Randomised controlled clinical trials in which at least 1 of the groups received dry needling were included. 662 studies were found; 14 clinical trials were selected for qualitative analysis and 13 for quantitative analysis. The quality of most of the studies included was “high.” All the studies reported improvements in cervical pain and/or disability, regardless of the protocol followed and the muscles targeted. No serious adverse effects were reported. Dry needling showed to be more effective when compared with other therapies in both women and men, without differences by sex. When the analysis was carried out by age, patients over 40 years old benefitted more than those below 40 years old. Our meta-analysis supports the use of dry needling to improve pain and functional capacity in patients with chronic neck pain at short- and mid-term intervals.